"SAFEGUARDING THE INTERESTS OF THE STATE" FROM DEFECTIVE DELINQUENT GIRLS. Issue 1 (26th November 2015) - Sohasky, Kate E.
Abstract : The 1911 mental classification, "defective delinquent, " was created as a temporary legal‐medical category in order to identify a peculiar class of delinquent girls in a specific institutional setting. The defective delinquent's alleged slight mental defect, combined with her appearance of normalcy, rendered her a "dangerous" and "incurable" citizen. At the intersection of institutional history and the history of ideas, this article explores the largely overlooked role of borderline mental classifications of near‐normalcy in the medicalization of intelligence and criminality during the first third of the twentieth‐century United States. Borderline classifications served as mechanisms of control over women's bodies through the criminalization of their minds, and the advent of psychometric tests legitimated and facilitated the spread of this classification beyond its original and intended context. The borderline case of the defective delinquent girl demonstrates the significance of marginal mental classifications to the policing of bodies through the medicalization of intellect.